Correlation of ST changes in leads V4–V6 to area of ischemia by CMR in inferior STEMI. (4th July 2018) - Jia, Xiaoming; Heiberg, Einar; Ripa, Maria Sejersten; Engblom, Henrik; Halvorsen, Sigrun; Arheden, Håkan; Atar, Dan; Clemmensen, Peter; Birnbaum, Yochai
Abstract: Objective. We aim to determine the correlation between ST-segment changes in leads V4–V6 and the extent of myocardial injury by cardiac magnetic resonance (CMR) in patients with inferior ST elevation (STE) myocardial infarction (iSTEMI). Design. Admission electrocardiogram and CMR data from the MITOCARE trial were used. Differences in mean myocardium at risk, infarct size, ejection fraction and myocardial segment involvement by CMR were compared in patients with first iSTEMI with STE, ST depression (STD) or no ST changes (NST) in V4–V6. Myocardial segment involvement was further evaluated by comparing proportion of patients in each group with ≥25% and ≥50% segment involvement. Results . Fifty-four patients were included. Patients with STE ( n = 22) and STD ( n = 16) in V4–V6 had significantly lower ejection fraction compared to NST ( n = 16) (48% vs 48% vs 54%, p = .02). STE showed more apical, apical lateral and mid-inferolateral involvement but less basal inferior involvement than NST. STD exhibited greater basal inferoseptal involvement compared to STE. There were more patients with STE that had ≥25% and ≥50% apical lateral involvement compared with STD and NST groups. Patients with STD were more likely to have ≥25% and ≥50% basal inferoseptal involvement compared with STE and NST groups. Conclusion. Our study suggests that in iSTEMI, ST changes in the precordial leads V4–V6 correlates with greater myocardial injury and distribution of myocardium at risk.